Interfacial reactions between solid Ni and liquid Sn–Zn alloys - Vanya Desimirova Gandova (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The limitation of the harmful lead-containing solders used in the electronics and other induistries apply change lead with another metals. Interfasial reactions between Sn-Zn alloys and Ni substrate after annealin at 400 0C and 450 0C were studied. Three intermetallic compounds Ni3Sn4, T1, gamma-Ni5Zn21 and liquid Sn were observed in the Ni/Sn-Zn diffusion couples. Scanning electron microscope was used for investigation samples. The microhardness measurement of the intermetallic layers was apply.